COMPETENCE ANALYSIS OF FASHION DESIGN CURRICULUM IN HIGHER EDUCATION SYSTEM IN TRANSITION ECONOMIES - Khurana, Karan; Riabchykov, M. (Problems of Engineer-Pedagogical Education, 2018)
The transition economies of today are striving to generate human resource in order to support the requirements of industrialization and developments. The governments of developing economies have essentially dedicated policies for capacity building to develop skilled labor in fashion and textile sectors. As we stream ahead in this development it becomes necessary to analyze if the design curriculums could support the need of generating skilled labor from existing education systems. This study aims to provide the students, academic organizations , teachers , industry and the stakeholders a very precise understanding on what subjects are taught in the courses and what importance do they serve finally. Further on, the aim of the work is to justify the rationality of the formation of general socio-cultural competence in the process of fashion education in studying the processes in developing economies. The analysis of curriculums is based on Competency-Based Education model which exhibits the credibility in various competence areas that are required to support the growth of developing economies and the individual in a multi-dimensional way. The curriculums are selected and studied from the two government universities in Ethiopia and Ukraine.